2013
DOI: 10.1136/sextrans-2011-050386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time since exposure toChlamydia trachomatison chlamydia antibody detection in women: a cross-sectional study

Abstract: Chlamydia antibody detection decreases with time since infection and this is most apparent in the first 6 months. In women who have had more than one infection, antibody remained detectable longer for all tests, but this was more marked for the pgp3 ELISA and MIF assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 19 publications
6
78
1
Order By: Relevance
“…For unknown reasons that are not precisely known, seropositivity reduces after months and may fade out in some people. 15 Accordingly, the seroprevalence found in our study is probably lower than the true incidence of C. trachomatis infection. However, because this fact is true as well as among the controls, as among the cases it does not weaken the observed result of the association between C. trachomatis seropositivity and ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…For unknown reasons that are not precisely known, seropositivity reduces after months and may fade out in some people. 15 Accordingly, the seroprevalence found in our study is probably lower than the true incidence of C. trachomatis infection. However, because this fact is true as well as among the controls, as among the cases it does not weaken the observed result of the association between C. trachomatis seropositivity and ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 81%
“…A peptide-based EIA test is considered to be the most sensitive and species specific, 19,20 and the assay used in our study (AniLabsystems) has been found the most sensitive commercial assay to detect antibodies after infection. 15 Reproducibility of the test in our study population was high (coefficient of intra-assay variation was 6.9% and coefficient of interassay variation was 6.5%). Correlation of the result between the AniLabsystems and another peptide-based method is greater than 0.9 indicating high specificity and sensitivity of the test.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Alternatively, women with TFI are more likely to have been exposed to repeat CT infections, which is associated with both reproductive damage (44,51) and with higher titers (46). For this reason we may regard the higher PEF estimate (43.0%, 95%CrI: 27.6, 57.5) as an upper bound as it ascribes the entire excess CT++ in cases to a causal mechanism rather than being partly or wholly the result of positive confounding.…”
Section: Discussionmentioning
confidence: 99%
“…We may speculate that the CT++ peak in the women without TFI might represent women who have had upper genital tract infection in whom inflammation has resolved, either following treatment or spontaneously, without causing tubal damage (6,45), as well as women with recent lower genital tract infections or re-infections, as the decline in antibody over time is far less marked in second infections (46). The excess CT++ seen in cases could simply be due to increased exposure to CT in women whose TFI was in fact caused by other sexually transmitted infections or bacterial vaginosis.…”
Section: Discussionmentioning
confidence: 99%